A utilização do kturtle nos processos de ensino e aprendizagem de uma escola pública do município de Assú-RN - Oliveira, Dolglas Tavares de (Universidade Federal Rural do Semi-Árido, 2020)
Digital Information and Communication Technologies (TDIC) are increasingly present in different areas of our society, whether in industry, commerce, health or education, since they can facilitate the production relationship of each of these sectors . In this perspective, our work had as a general objective: Investigate whether the program is able to contribute to the teaching and learning processes of students, especially in the subjects of Portuguese and mathematics through a course using the K-turtle software. As specific objectives we had: (i) Investigate whether programming can be a fun way in the students' teaching and learning processes; (ii) Identify whether the computers in the computer lab can be study tools. The methodology used in this work was a field research in the city of Assú, located in the Western region of the State of Rio Grande do Norte, at the State School Poeta Renato Caldas - CAIC. In our first moment at school, we applied a questionnaire (subjective questions) to students who showed interest in participating in the programming course, in order to assess the level of knowledge of students in relation to programming as an aid tool in the teaching and learning processes . It was possible to conclude that the K-turtle software can contribute to the teaching and learning processes, being seen as another tool to be available as others that enter the field of TDC's, considering that there were contributions to the contents of the subjects of Portuguese and mathematics being taught in a more playful way, breaking some traditional concepts rooted by a small percentage of teachers that still exist.
Monografia
Keywords: Tecnologias Digitais da Informação e Comunicação; Processos de Ensino e aprendizagem; Kturtle; Digital Information and Communication Technologies; Teaching and learning processes.; Kturtle; CIENCIAS EXATAS E DA TERRA::COMPUTACAO E INFORMATICA